Preserved visuoconstruction in patients with Alzheimer's pathology and anti-neural autoantibodies: A case control study - Hansen, Niels; Hirschel, Sina; Teegen, Bianca; Wiltfang, Jens; Malchow, Berend (Frontiers in Dementia, 2022)
Background Alzheimer´s disease (AD) is seldom reported to be associated with neural autoantibodies apart from those involved in axonal neurodegeneration and amyloidopathy in prior studies. Nevertheless, this is an under-investigated aspect of AD. As we do not know whether additional screening for autoantibodies in AD patients has additional diagnostic and therapeutic value, this study aims to shed light on whether visuoconstructive or figural memory capacities might distinguish these patient populations. Methods In this pilot case series, we investigated eight patients suffering from cognitive impairment associated with cerebrospinal fluid (CSF)-based Alzheimer pathology (AP) and with verified anti-neural autoantibodies (AP Aab+) compared to eight AD patients presenting no autoantibodies (Aab-) (AD Aab-). Patients files were reviewed retrospectively regarding their neuropsychological profile assessed via the CERAD (Consortium to Establish a Registry for Alzheimer's Disease) test battery and psychopathology measured by the AMDP (Manual for the Assessment and Documentation of Psychopathology in Psychiatry) system. We also relied on diagnostic parameters as in the CSF and magnetic resonance images. Results All patients shared the same pattern of dysfunctional word-list learning and word-list recall resembling a hippocampus-dependent memory dysfunction. Furthermore, both patient groups revealed a CSF profile concurring with Alzheimer´s disease. However, visuoconstructive capacity, but not figure recall was preserved in AP Aab+ patients, but not in AD Ab-patients with the shared hippocampus-based memory dysfunction. We observed no relevant differences between the AP Aab+ and AD Aab- groups in CSF cell-counts or intrathecal IgG synthesis. The relative frequency of hippocampal and focal atrophy did not differ either between AP Aab+ and AD Aab- groups. Discussion Our pilot findings are encouraging us to conduct large-scale studies to replicate our discovery of preserved visuoconstruction in AP Aab+ patients with hippocampus-based memory dysfunction. The role of anti-neural autoantibodies is still not fully understood. The detection of these autoantibodies might imply another disease pathology that could be either neuroprotective or be affecting other brain regions, ie, less pronounced disease activity in the right temporo-parietal regions mainly involved in visuoconstruction.